The phosphodiesterase PdeB regulates the colonization behavior of Shewanella putrefaciens CN-32 and localizes at the cell pole with its GGDEF domain - Rick, Tim; Justus Liebig University Giessen (My University, 2021)
The nucleotide messenger cyclic diguanylate (c-di-GMP) regulates numerous cellular processes in gram-negative bacteria, such as motility, biofilm formation, virulence and cell cycle. The production of this messenger is catalyzed by diguanylate cyclases (DGCs) which harbor a GGDEF domain, while c-di-GMP specific phosphodiesterases (PDEs) mediate its degradation with their EAL- or HD-GYP domains. Most bacteria encode a plethora of enzymes that can potentially affect the production or degradation of this messenger. The model organism that was used in this study, Shewanella putrefaciens CN-32, encodes 52 proteins that harbor such domains. The sheer amount of these enzymes demands a strict spatial and temporal organization of c-di-GMP signaling. This work provides novel insights into the spatiotemporal control of c-di-GMP signaling and illuminates the mechanism of a novel function of the inhibitory site of GGDEF-domains in GGDEF-EAL proteins. The c-di-GMP-degrading enzyme PdeB harbors a GGDEF and an EAL domain in its cytoplasmic portion. Additionally, it has a HAMP/PAS module and two transmembrane domains that flank a long periplasmic region. It was found that the GGDEF domain is enzymatically inactive but obtained a novel function by localizing the protein to the cell pole. This process is mediated by a direct protein-protein interaction with the polar landmark protein HubP. Here, we identified that the inhibitory site of the GGDEF domain interacts with the far C-terminal region of the landmark protein HubP and suspect that this interaction alters the aggregation state of HubP. These results provide further insights into the complex mechanisms of the landmark protein-mediated polar localization of proteins, which is of great interest since homologues of HubP are present in numerous pathogenic bacteria. The interaction with HubP is required for full PDE activity of PdeB. We observed that PdeB affects bacterial motility by regulating the lateral flagella on a transcriptional and post translational level. Additionally, PdeB affects the assembly of MSHA-pili by regulating the activity of the extension ATPase MshE. This protein binds c-di-GMP directly with its N-terminal domain, while the second type IV pilus system is not affected. PdeB was also found to negatively regulate the production of Bpf surface adhesion proteins by repressing their transcription. We found that the PDE activity of PdeB is regulated by multiple signals. The GGDEF domain needs to interact with the landmark protein HubP and binds GTP to its active site to fully induce the PDE activity of the EAL domain. We suspect that both processes rearrange the hinge-helix that connects both domains. Additionally, the results indicate that the periplasmic region of PdeB binds an unknown extracellular ligand. Accordingly, we found that the periplasmic region of PdeB is also required for full PDE activity. Combining the results of the polar localization of PdeB and the influence on motility and biofilm factors we postulate that the polar localization generates heterogeneity in the population and governs an efficient colonization strategy of new environments, similar to the previously proposed “touch-seed-and-go” model.
Keywords: c-di-GMP; ddc:570